Effect of piezoelectric technique on auditory function on postoperative day one in septorhinoplasty surgery - İlhan, Adem Emre; Durna, Yusuf Muhammed; Tekin, Ahmet Mahmut; Yılmaz, Fahrettin; Yılmaz, Yetkin Zeki (Lippincott Williams & Wilkins, 2018)
Aim: To examine the effect of the piezoelectric application used increasingly for osteotomy and correction of nasal dorsum in septorhinoplasty surgeries on early auditory functions. Methods: Our study was conducted after the decision of 10840098604.01.01- E. 9057 taken from Istanbul Medipol University Clinical Research Local Ethics Committee. This study was designed to be prospective, randomized and controlled. Twenty patients between 18 and 50 years of age that piezoelectric technique was used in the study group and 10 patients in the same age range who underwent nasal surgery (endoscopic sinus surgery, septoplasty, lower concha radiofrequency and nasal valve surgery) for any reason in the control group were included in the study. Audiologic functions of the patients in both the groups were assessed by pure audio audiometry, tympanometry and distortion product otoacoustic emission test before the surgery and 24 hours after the surgery. The data obtained were statistically compared using the SPSS 22.0 program and P<0.05 was considered significant. Results: Twenty patients (5 males, 15 females) that piezoelectric (ultrasonics) technique was used during septorhinoplasty in the study group and 10 patients (5 males, 5 females) in the control group were included in the study. In the study and the control groups, preoperative and postoperative air/bone path thresholds at the right and left ears did not differ significantly (P>0.05) at 250, 500, 1000, 2000, 4000, 6000, and 8000Hz. The results of distortion product otoacoustic emission results (signal/noise ratio) obtained postoperativelywere not statistically significant (P>0.05) with the results obtained preoperatively. Conclusion: The results of the study show that the piezoelectric technique used in septorhinoplasty does not cause a negative effect on auditory functions. This study is the first comparative study to investigate the effect of piezoelectric technique used in septorhinoplasty surgery on auditory functions. After further clinical studies performed with well- selected and large patient population, the piezoelectric techniques can be a preferred technique during septorhinoplasty operations.
WOS: 000467707800009
PubMed ID: 29927822
Keywords: Otoacoustic Emission; Osteotomy; Piezoelectric; Pure Tone Audiometry; Rhinoplasty